Günümüz Türk toplumunda dinsellik ve kadın/erkek aleyhtarı tutumlar - Uysal, Veysel (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2001)
Religiosity in the Contemporary Turkish Society and Anti-feminist Attitudes This article studies the process of change in personal and social life in relation to traditional and modem values. In another words, different approaches to man and woman which are resulted from Islamic and traditional culture have been highlighted. Observations rnade in the modem society indicates that patterns of behaviour have changed. In particular the changes of attitude regarding women' s status and role in society. Hence, we will study the relationship between independent variables (sex, age, education, incorne, locality) and dependerit variables (attitudes towards women)